In Search of Alternative to Inductionism (K. Popper’s Philosophy of Science) - Nekrašas, Evaldas (Problemos, 1977)
The article offers a critical analysis of K. Popper’s philosophy of science. Prominence is given to the consideration of Popper’s anti-inductivism and a comparative analysis of K. Popper’s philosophy of science and the philosophy of science of logical empiricism. At first the article deals with the solution of the problem of induction suggested by Popper, a falsificative criterion of the demarcation of science, and Popper’s conception of the growth of scientific knowledge. On the one hand, the proximity is noted of theoretical premises from which Popper and logical empiricists proceed, on the other, the originality of some of Popper’s methodological solutions (in comparison with the conceptions of logical empiricists) is appreciated, in particular the distinction of the problems of sense and demarcation, and the consideration of the problem of the foundation of knowledge within the framework of diachronic analysis. An assumption considering conventionalism as an actual alternative to inductivism in Popper’s philosophy of science is founded.